MORPHOMETRIC SUMMARY FEATURES INDICATORS OF TERMINAL VILLI IN PRETERM PLACENTA - Kurbonova Bashorat Mustafaevna (Western European Studies, 2024)
In this study, morphometric features of terminal villi in term and preterm placentas were compared.Places of the cent of 35 patients whose pregnancy ended in premature birth and placentas of 30 women with physiological pregnancy and delivery at term were studied. Morphometric assessment was made with Carl Zeiss Axio Imager microscope using an image analysis software package. The number of capillaries in terminal villi of preterm placentas was found to be decreased, while the vessels-to syncytiotrophoblast distance was found to be increased. These results in a fell gas exchange between maternal blood and placental tissue, hypoxia and can cause early terminationof pregnancy
Keywords: morphometry; placenta; placentapre- maturity